2012
DOI: 10.1101/cshperspect.a008664
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Nonapoptotic Caspase Functions in Animal Development

Abstract: A developing animal is exposed to both intrinsic and extrinsic stresses. One stress response is caspase activation. Caspase activation not only controls apoptosis but also proliferation, differentiation, cell shape, and cell migration. Caspase activation drives development by executing cell death or nonapoptotic functions in a cell-autonomous manner, and by secreting signaling molecules or generating mechanical forces, in a noncell autonomous manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 157 publications
2
52
0
4
Order By: Relevance
“…These results agree with the findings reported in previous studies where caspases have been revealed as dynamic regulatory molecules during cell differentiation (in neural cells and salivary gland in drosophila), cell morphology, stem-cell maintenance, tissue regeneration and actin-cytoskeleton reorganization (38)(39)(40)(41). On the contrary, Kouidhi et al (32) demonstrated the absence of caspase 3 at PNDs 21 and 35 in their study.…”
Section: Figsupporting
confidence: 93%
“…These results agree with the findings reported in previous studies where caspases have been revealed as dynamic regulatory molecules during cell differentiation (in neural cells and salivary gland in drosophila), cell morphology, stem-cell maintenance, tissue regeneration and actin-cytoskeleton reorganization (38)(39)(40)(41). On the contrary, Kouidhi et al (32) demonstrated the absence of caspase 3 at PNDs 21 and 35 in their study.…”
Section: Figsupporting
confidence: 93%
“…Whether other cell-death proteases can be upregulated in a similar manner is a question in a long list of questions which warrant further investigation in order to decipher the underlying interconnections behind the mutual crosstalk of autophagy and apoptosis. Since caspases have been known to contribute to processes such as cellproliferation and differentiation, which are starkly contradictory to apoptosis [3], [117], [118], it is entirely possible that these misunderstood hitmen may have additional and more extensive roles in autophagy awaiting discovery. Taking all the presented findings into account, the primary conclusions of the review are that caspases can directly interact with known ATGs and consequently affect autophagy in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 3 activation has also been found to coincide with ephrin-induced EphA4 activation, albeit in an apoptotic situation (Park et al, 2013). Although Eph activation-induced apoptosis might play a role during neural development (Depaepe et al, 2005;Duffy et al, 2008), we have demonstrated previously that in EphA3-HEK293 and melanoma cells ephrinA5-induced cell contraction does not induce apoptosis (Lawrenson et al, 2002), indicating that localised caspase-3 activation and PTP-PEST cleavage in ephrin-stimulated EphA3-HEK293 cells reflects one of the non-apoptotic caspase functions that have been previously described (Miura, 2012).…”
Section: A Caspase-cleaved Ptp-pest N-terminal Ptp Fragment Controls mentioning
confidence: 99%